AL IHTILAF AL-FIQHI WA TAUDZIF FI QADHAYA MA`ASHIRA - Athambawa, Mahroof (Indonesian Journal of Islamic Literature and Muslim Society, 2019)
This research  Paper Studies the issue of "jurisprudence differences" and ways of Employing them in contemporary issues, which is an important issue in the present day, Because There  are People such as Orientalists and Prejudiced who view the reality of jurisprudence differences as a gap that defects the structure of Islamic jurisprudence and then come to the conclusion that it is merely comprising  a group of human thoughts and not a living revelation from Almighty God as it is believed ,However, the reality that should not be forgotten by the Thinker who is free from intellectual biased precedents, that the jurisprudential differences arising from the derivation of the scholars who had profound knowledge with the sincerity of religious commitment and Devotion to God is the Outcome of approach intended By Allah and used to Derive  Islamic Judgments from the Quran and the Sunnah. Jurisprudential differences are a function established  by the god for the scholars  in order to take care of the interests of the people and fulfill their innate needs, but the question arises what are the best approaches to take advantage of this rich scientific heritage in our contemporary issues, this  research provides a detailed treatment of this issue and lead to the results that can be utilized in the development of jurisprudential work in the present day.